2020
DOI: 10.3389/fmicb.2020.01848
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Absence of Electron Transport Chains in Patescibacteria and DPANN

Abstract: Recent discoveries suggest that the candidate superphyla Patescibacteria and DPANN constitute a large fraction of the phylogenetic diversity of Bacteria and Archaea. Their small genomes and limited coding potential have been hypothesized to be ancestral adaptations to obligate symbiotic lifestyles. To test this hypothesis, we performed cell-cell association, genomic, and phylogenetic analyses on 4,829 individual cells of Bacteria and Archaea from 46 globally distributed surface and subsurface field samples. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 90 publications
(176 reference statements)
8
59
0
Order By: Relevance
“…4b ). Owing to their small cell size (average ~0.2 µm diameter 47 ), a CPR/DPANN cell present in the 2.5+ µm or 0.65–2.5 µm fraction is probably attached to a larger organism, whereas a CPR/DPANN cell present in the 0.1–0.2 µm fraction is probably unattached. Substantial coverage of CPR/DPANN genomes in the 2.5+ µm and 0.65–2.5 µm fractions indicate that a fair number of CPR/DPANN cells retain host attachment throughout the filtration process, and we consider it probable that pili penetrating from ultrasmall cells into the host (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b ). Owing to their small cell size (average ~0.2 µm diameter 47 ), a CPR/DPANN cell present in the 2.5+ µm or 0.65–2.5 µm fraction is probably attached to a larger organism, whereas a CPR/DPANN cell present in the 0.1–0.2 µm fraction is probably unattached. Substantial coverage of CPR/DPANN genomes in the 2.5+ µm and 0.65–2.5 µm fractions indicate that a fair number of CPR/DPANN cells retain host attachment throughout the filtration process, and we consider it probable that pili penetrating from ultrasmall cells into the host (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of replication-rate analysis and with cryo-TEM imaging of dividing host-attached ultrasmall cells, higher CPR instantaneous replication rates are associated with physical attachment to hosts, suggesting that the availability of host-supplied resources may stimulate replication of CPR organisms. One recent study instead concluded that there is no widespread attachment of CPR bacteria to hosts on the basis of failure to detect co-occurring CPR and host genomic signatures in SAGs 47 . However, we believe the incompleteness of the reported SAGs and the small absolute number of organisms analysed per site render the results inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the phyla in which heme biosynthetic pathway gaps were frequent consisted of not-yet or rarely cultured organisms, the so-called microbial dark matter 32 , suggesting that heme auxotrophy is a plausible explanation for the challenges of culturing the uncultured microbial majority. Alternatively, considering the enormous metabolic diversity of prokaryotes, unknown heme biosynthesis pathways are a possibility, and several of the groups predicted to be heme-auxotrophs (e.g., Patescibacteria and DPANN) are inferred from their genomes to lack respiration and rely strictly on fermentative metabolism 33,34 ; these cells could conceivably replicate with little to no exogenous heme.…”
Section: Figmentioning
confidence: 99%
“…Phylogeny-oriented (phylocentric) studies, on the other hand, focus on characterizing genomes belonging to a specific lineage of interest, with the aim of delineating its pan, core, and dispensable gene repertoire, documenting the defining metabolic capabilities and physiological preferences for the entire lineage and encompassed clades 7,8 , understanding the lineage's ecological distribution and putative roles in various habitats 4,9 , and elucidating genomic basis underpinning niche specializing patterns 10 . The scope of phylocentric studies could range from the analysis of a single genome from a single ecosystem 11 , to global sampling and in-silico analysis efforts 12,13 .…”
Section: Introductionmentioning
confidence: 99%